Identification of molecular markers for Thinopyrum distichum chromosomes contributing to salt tolerance - Badenhorst, Petrus Cornelius (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc.)--University of Stellenbosch, 2000.